Study of the physical environment of selected preschools in Quezon City a basis for designing educational environments - Buencamino, Lorena; Florendo, Raquel B. (2001)
The purpose of this study is to examine the physical environment of six preschool establishments and observe what guidelines are being used in the design conceptualization in their classrooms. Included in the study are three preschools from Montessori program and three from a Progressive program. The selection was based on those establishments located with Quezon City and with tuition fee that ranges between twenty to thirty thousand pesos annually. The objectives of this study intend to know the philosophy and goals of the preschools; to observe the physical environment; to identify the daily activities of the children; to evaluate whether philosophy and goals are expressed in the design; and to recommend a process towards a design approach of the physical environment. A video camera, for recording of daily activities and documentation of the physical surrounding was used for this study. In addition, other information were gathered from interviews from teachers and reference materials on early childhood education. At the same time, floor plants with furniture layout, schematic diagrams and environmental matrices were formulated to arrive at spatial organization, traffic flow and furniture requirements. The Gestalt psychology was used in analyzing the overall design conceptualization while taking into consideration the philosophy and goals of the school. Moreover, Proxemics was used to identify spatial organization and relationship of activities and learning spaces. Finally, basic design components were used in the assessment of the background environment such as, floors, wall and ceiling. The results of the study indicate that most preschool establishments and their teachers try as much as possible to emulate the philosophy and goal of the school into the overall design and conceptualization of their classrooms. However, rental policy and spatial constraints, economic hindrance and lack of particulars on the basic design components have a bearing on the uncompromising design of the physical environment.
Research project funded by the university through the Office of the Vice-Chancellor for Research and Development (OVCRD).
"May 2001."
Thesis (M. Interior Design)--University of the Philippines Diliman.
Keywords: Nursery schools -- Philippines -- Quezon City -- Designs and plans; Education, Preschool -- Philippines -- Quezon City